2006
DOI: 10.1080/14616730600594450
|View full text |Cite
|
Sign up to set email alerts
|

Attachment linked predictors of women's emotional and cognitive responses to infant distress

Abstract: The purpose of this study was to examine associations among women's emotional and cognitive responses to infant fear and anger and to identify attachment linked predictors of these responses. Four hundred and forty Caucasian and African American undergraduate college women viewed video clips of two crying infants, one displaying anger and the other displaying fear. They identified what the infants were feeling, made causal attributions about the cause of crying, rated their own emotional reactions to the cryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 58 publications
3
84
3
Order By: Relevance
“…The Video Ratings (VR; Leerkes and Siepak 2006) involve two 1-min videos depicting babies crying while playing with a toy. After each video, 18 questions are presented on which participants rate their attributions for the baby crying on a 4-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…The Video Ratings (VR; Leerkes and Siepak 2006) involve two 1-min videos depicting babies crying while playing with a toy. After each video, 18 questions are presented on which participants rate their attributions for the baby crying on a 4-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…For example, maternal insecurity was related to less sensitive and comforting responses to child distress following a medical procedure (Edelstein et al, 2004; Goodman et al, 1997). In addition, Leerkes and Siepak (2006) found that attachment insecurity, particularly avoidance, was associated with more negative responses to videos of infant distress in a sample of female undergraduates without children.…”
Section: Introductionmentioning
confidence: 94%
“…In this study, we focus on four non-supportive emotion socialization practices that have been included across a number of prior studies: (a) minimizing which includes telling a child not to over-react or be so upset; (b) punishment which includes scolding or disciplining a child for being upset, (c) teasing which includes calling a child names or ridiculing them for being upset, and (d) ignoring a child when upset (Fabes, Poulin, Eisenberg, & Madden-Derdich, 2002; Klimes-Dougan et al, 2007, Leerkes & Siepak, 2006). Each of these practices serve the apparent goal of coercing children to suppress or reduce their display of negative emotions in the moment with little attention to the long-term implications for children's autonomous regulation of emotions.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that the appropriateness and hence effect of parents’ non-supportive emotion socialization on children's subsequent emotional adjustment varies by ethnicity because of different socio-cultural experiences and expectations (Cole & Tan, 2007; Ogbu, 1981). Specifically, non-supportive emotion socialization is more normative in African American families (Halberstadt, Craig, Lozada, & Brown, 2011; Leerkes & Siepak, 2006; Montague et al, 2003; Nelson et al, 2012) and may be a deliberate effort to teach children to minimize their emotions in an effort to protect them from racism (Garrett-Peters et al, 2008, 2011; Nelson et al, 2012). If African American children accurately perceive that their parents engage in non-supportive responses to their negative emotions in an effort to protect them from discrimination (by recognizing that the expression of negative emotions may be interpreted negatively by European Americans), they may view this as evidence of their parents’ love and concern; a feeling that should be reinforced by the within-group normativeness of this behavior.…”
Section: Introductionmentioning
confidence: 99%